The Parody of the Commons - Vasilis Kostakis; Stelios Stavroulakis (tripleC: Communication, Capitalism & Critique)
This essay builds on the idea that Commons-based peer production is a social advancement within capitalism but with various post-capitalistic aspects, in need of protection, enforcement, stimulation and connection with progressive social movements. We use theory and examples to claim that peer-to-peer economic relations can be undermined in the long run, distorted by the extra-economic means of a political context designed to maintain profit-driven relations of production into power. This subversion can arguably become a state policy, and the subsequent outcome is the full absorption of the Commons as well as of the underpinning peer-to-peer relations into the dominant mode of production. To tackle this threat, we argue in favour of a certain working agenda for Commons-based communities. Such an agenda should aim the enforcement of the circulation of the Commons. Therefore, any useful social transformation will be meaningful if the people themselves decide and apply policies for their own benefit, optimally with the support of a sovereign partner state. If peer production is to become dominant, it has to control capital accumulation with the aim to marginalise and eventually transcend capitalism.